Study on die shoulder patterning method (DSPM) to minimise springback of U-bending - Baharuddin, N. J.; Ahmad Rosli, Abdul Manaf; Ahmad Shahir, Jamaludin (Penerbit Universiti Malaysia Pahang, 2022)
U-bending is increasingly used in the sheet metal industry such as car door pillars. However, springback phenomenon always tends to occur after removing sheet metal from the fixtures and resulting in changing product effectiveness, wasting material as well as increasing manufacturing costs. Thus, minimizing springback in the bending of sheet metal is vital to maintain close geometric tolerances in the deformed part. Many researchers have done investigated and predicted the springback occurrence by experiments and simulations. Neverthessly, there is no actual study on the die shoulder patterning method (DSPM) to reduce springback of hat-shaped parts. In this paper, the hat-shaped part is deformed using the new developed forming method and have been experimented with as well as validated using three-way Anova and graphical analysis. As expected, DSPM dominates the springback sensitivity, with higher contact area reducing the springback of hat-shaped parts. For AISI 1030 of pattern 2, springback is dramatically reduced as the sliding stress between the die shoulder and surface of the blank is optimized.